Hubungan Pemahaman Teks Keagamaan Dengan Terbangunnya Karekter Toleransi dan Munculnya Faham Radikalisme - Suaidi Suaidi (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2023)
Islam the religion that was revealed brought messages of peace, humanity which was summed up in the term "Rahmatan Lil' Alamiin". Indeed, every Muslim is able to crystallize the teachings of Islam as a manipulated soul in a peaceful and harmonious manner. Muslims who manipulate Islam as Rahmatan Lil 'Alamin in daily behavior are also able to dismiss the assumption that Islam is synonymous with violence, radicalism and terrorism. The truth is indisputable because wherever there is violence, terrorism, radicalism symbolized by bomb explosions, it can be ascertained that the perpetrators use Islamic shimbols such as wearing Muslim clothes or Muslim women. This is contrary to the goal of sending Islam to the earth. Islam strongly condemns this form of violence for whatever reason. The core teachings of Islam are developed with peace, harmony, tolerance and obligatory to maintain the five elements (1) Safeguarding Religion, (2) Safeguarding Intellect, (3) Safeguarding the Soul, (4) Guarding Offspring and (5) Safeguarding Property. These five foundations do not apply only to internal Muslims but also to people of different beliefs (between religious ummah). The attitude of a Muslim in the reflection of his daily life must develop a life of tolerance, mutual respect and respect. This study aims to provide answers as well as explore the causes of a small part of the behavior of Muslims who hack the path of violence, inhumane and intolerant.